Participation of previously landless in farmer companies under the LUSIP project in Swaziland - Simelane, Lunga (My University, 2014)
This study set out to examine tenure arrangements under the LUSIP project in Swaziland, wherein people have been made to forego their land rights and form farmer companies to which they would be equal shareholders with previously landless households’ representatives. In this regard, it sought to understand the relations that unfold between these two sets of shareholders, with a particular focus on the level of participation of the previously landless in their role as equal shareholders. Three FCs in Sibhotela, a section in the Madlenya chiefdom which forms part of the project development area, were selected for study in the research. To ground it on theory, the study has drawn on literature around land tenure systems and their implications for social inclusion. Through the use of qualitative methods, data was collected and particular findings were made and analysed. The findings made in the study reflect that indeed the previously landless are in many ways marginalized by the previous agricultural plot owners in their participation as shareholders in the FCs. An analysis of the findings reflects that the incorporation of the previously landless has worked in terms of assisting them to have some form of income. However, it has not empowered them to meaningfully participate in the decision-making processes within the FCs. The study therefore draws the conclusion that participation of the previously landless in the farmer companies that were formed under the auspices of LUSIP is compromised at the level of the operations and decision-making. With the FCs having started operations in the year 2008, the study has identified an opportunity for further research into the elements or factors that have sustained these FCs for the period they have been in operation.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.